BIBLIOMETRIC ANALYSIS STUDY OF DEMOGRAPHIC DIVIDEND ON INDONESIA ECONOMYC GROWTH: A TREATH OR AN OPPORTUNITY? A SYSTEMATIC LITERATURE REVIEW - Syauqi Agung Firmanda; Dwi Nur Laili Paramita; Febria Rima Wardah (Jurnal Development, 2025)
The Demographic Dividend can influence the course of a country's economy. This literature aims to provide a view and recommendation on the existence of Demographic Dividend on Indonesia's economic growth, which is based on empirical information and actual conditions currently occurring in Indonesia. This literature used a Systematic Literature Review approach using 12 article references, which were then visualized and used data crawling with Bibliometric techniques on the VosViewer analysis tool. The results of the analysis showed that there was a strong relationship between Demographic Dividend and Economic Growth. The Demographic Dividend can be both an opportunity and a threat based on the level of skills and knowledge of the working-age population. The important factor in managing the Demographic Dividend were improving the quality of human resources through competency-based education, improving infrastructure, improving public facilities, structural reform, and managing the Demographic Dividend based on Environmental Sustainability. Therefore, the government needs to establish targeted regulations to take advantage of Demographic Dividend opportunities to increase economic growth in the future